Preparation and characterization of novel multi-branched polymers in situ cured from benzoxazine/epoxy resin/primary amines blends. Issue 18 (5th February 2016) - Wang, Hongyuan; Yang, Po; Zhu, Rongqi; Gu, Yi
Abstract : Novel high-performance multi-branched copolymers were prepared in situ from benzoxazine, epoxy resin and primary amines through controlling the curing reactions. Abstract : High performance polymers with multi-branched structures were prepared in situ from ddm-based benzoxazine (M), cycloaliphatic epoxy resin (T) and diaminodiphenylmethane (ddm) or hexamethylenediamine (6a) via controlling the curing reaction sequence of the system. The curing behavior, cross-linked structures and properties of the system were investigated by differential scanning calorimetry (DSC), Fourier transform infrared (FTIR), dynamic mechanical analysis (DMA) and mechanical properties test, respectively. The results suggest that the reaction between T and ddm or 6a was more easily processed than that of M and ddm or 6a, and the multi-branched polymers can be formed in situ in a ternary system based on M, T and ddm or 6a. The heat resistance and mechanical properties of the cured resins with multi-branched structures were greatly improved compared with the polybenzoxazine or poly-benzoxazine/epoxy resin systems. The obtained results provide a new approach to control the chemical cross-linked structures and properties of polybenzoxazines.